Pengaruh Kompensasi dan Employer Branding Terhadap Minat Melamar Kerja pada Generasi Z di Kota Pekanbaru - Siti Marwah (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study analyzes the influence of compensation and employer branding on the interest in applying for jobs among Generation Z in Pekanbaru City amidst the war for talent phenomenon. The study aims to demonstrate the importance of competitive compensation and a positive corporate image in attracting potential applicants. The method used is a quantitative approach, involving 270 participants from Generation Z in Pekanbaru. Data were collected through questionnaires and analyzed using multiple linear regression techniques. The research findings indicate that both compensation and employer branding have a positive and significant influence, both individually and simultaneously, on interest in applying for jobs. The Adjusted R Square value of 0.783 indicates that these two factors explain 78.3% of the variation in interest in applying. These results emphasize the importance of strengthening compensation strategies and corporate image to increase organizational attractiveness.